Pengaruh Substitusi Abu Cangkang Sawit Terhadap Kuat Tekan Beton - Vike Itteridi; Rusandinata (JURNAL ILMIAH BERING'S, 2018)
This research was conducted to determine the effect of substitution of palm shell ash mixture on concrete compressive strength. In this case the use of the mixture was made with as many as 9 tests and using 2 variations of concrete age 3 days and 28 days with concrete quality planning f'c = 20 mpa. Based on the results of research in the laboratory, the concrete compressive strength using Palm Shell Ash at 28 days is 20.59 mpa. The robustness of a building is greatly influenced by the quality of the concrete quality, in order to know the quality of a concrete first there is a more careful planning and supervision of the materials to be used. So far, no research has been carried out in the Pagar Alam City Area by removing the Palm Shell Ash.